2001
DOI: 10.1093/jn/131.12.3251
|View full text |Cite
|
Sign up to set email alerts
|

Genistein Modulates Immune Responses and Increases Host Resistance to B16F10 Tumor in Adult Female B6C3F1 Mice

Abstract: The isoflavone genistein (4,7,4'-trihydroxyisoflavone) is a phytoestrogen found in high levels in soy products that has been associated with decreased incidences of breast and prostate cancers. The potential effects of genistein on the immune system were evaluated in adult female B6C3F1 mice. Groups of mice were exposed to vehicle or genistein by gavage for 28 d. The doses of genistein used were 2, 6 and 20 mg/kg body. Consistent with the chemopreventive effect of genistein, exposure to this compound significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(82 citation statements)
references
References 32 publications
4
77
1
Order By: Relevance
“…Although genistein increased IgM at the dose of 6 mg/kg in adult female B6C3F1 mice, no effect was observed in the high dose group. Furthermore, exposure to genistein had no effect on IgG response [23]. Oral administration of daidzein to Swiss mice increased the thymic mass and number of lymphocytes in blood and resulted in elevated antigen-specific IgM [24].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Although genistein increased IgM at the dose of 6 mg/kg in adult female B6C3F1 mice, no effect was observed in the high dose group. Furthermore, exposure to genistein had no effect on IgG response [23]. Oral administration of daidzein to Swiss mice increased the thymic mass and number of lymphocytes in blood and resulted in elevated antigen-specific IgM [24].…”
Section: Discussionmentioning
confidence: 93%
“…The functions of T cells and NK cells were altered after oral exposure to genistein at physiologically relevant concentrations in experimental animals. Specifically, exposure to genistein in adult female mice for 28 days by gavage increased the activities of cytotoxic T cells and NK cells [23].…”
Section: Discussionmentioning
confidence: 96%
“…It is worthy to underline that soy is found in up to 60% of processed food, being a food additive and a meat substitute. Genistein and daidzein are the two most well characterized isoflavones [19,20].…”
Section: Effects Of Environmental Estrogens On the Immune Systemmentioning
confidence: 99%
“…Using a high performance liquid chromatography, we previously estimated that the levels of the glycoside types of genistein and daidzein in NSBP are 20.7 and 35.4 ppm, while the levels of the aglycone types are 118.0 and 188.0 ppm, respectively. Zhang et al reported that daidzein enhances the phagocytic activity in mice (27), while Guo et al reported that genistein increases the activity of cytotoxic T cells and NK cells in mice (28). It is demonstrated that the content of total daidzein and genistein of the fermented soybean without salt was increased more than that with 10% salt, presumably resulting from the low level of metabolical activation of Aspergillus oryzae under such a high salt content (29).…”
Section: Cd4mentioning
confidence: 99%